A survivable and cost-effective IP metro interconnect architecture. - Veitch, P. (IEEE Communications magazine)
Due to volatile market conditions and increased competition, network operators and Internet service providers have been put under enormous pressure to cut costs while providing the same if not better levels of service to customers. Several aspects of network design are subject to review to assess possible cost savings while maintaining service levels and reliability. This article focuses on Internet protocol network infrastructure design, and in particular investigates architectural options for interconnecting small "IP metro" PoPs to an "IP core" PoP. The baseline architecture is characterized by dual uplink circuits from the metro to the core PoP. Three variants of an alternative architecture based on a single uplink circuit from the metro to the core PoP are compared against the baseline network in terms of end-to-end availability/downtime and capital cost.